Пиранья. Охота на олигарха: [роман] / А. Бушков - Бушков Александр Александрович (ОЛМА Медиа Групп, 2014)
Экземпляры: ф.1 (20210225☮) / Инвентарный номер: 60894 / Цена: 20.00 / Авт.знак: Б 94 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6